Updates on bisphosphonates and potential pathobiology of bisphosphonate‐induced jaw osteonecrosis - J Sarin; SS DeRossi; SO Akintoye (Oral Diseases, 2008)
Osteonecrosis of the jaws is a major complication associated with long‐term use of bisphosphonates. While osteonecrosis can arise from other precipitating conditions, bisphosphonate‐induced jaw osteonecrosis (BJON) is highly associated with long‐term administration of pamidronate (Aredia ® ) and zoledronic acid (Zometa ® ), which are two intravenous bisphosphonate formulations. The underlying pathogenesis of BJON and its site‐specific presentation still remain to be fully elucidated. This review will discuss clinically available bisphosphonates, current opinions, pathogenesis, and management guidelines for bisphosphonate‐induced jaw osteonecrosis.